A nutshell model of labor demand with permanent and short-term contracts - Contini, Bruno (Bonn, 2019)
"The paper presents a two-period "nutshell" model that explains the composition of labour demand when the labour market is dualistic and workers may be hired via permanent (P) or temporary (T) contracts. The model does not explain the level of labor demand, nor the wage of permanent workers, assumed to be exogenous. This is the main difference with the more sophisticated structural model of Bentolila et al. (2012) where employment and wages are jointly determined. The nuthsell model delivers, however, a number of easily testable hypotheses – very relevant for policy – that the structural model does not handle."